Effects of cyclophosphamide on murine candidiasis. - Moser, S A (1980)
Male CBA/J mice were given a single dose of 200 mg of cyclophosphamide (CY) per kg 3 days before a first or second cutaneous inoculation with viable Candida albicans in an attempt to suppress antibody formation and determine the effects of such suppression on the development of acquired immunity. After cutaneous inoculation, mice not treated with CY developed acquired immunity to intravenous challenge, which was accompanied by the development of circulating antibodies, delayed hypersensitivity, and in vitro responsiveness of lymph node cells to Candida antigens. CY treatment resulted in an immediate depression of peripheral blood leukocytes, with polymorphonuclear leukocytes and monocytes rebounding quickly to normal or above normal levels while lymphocyte remained depressed throughout the 4-week observation period. In vitro stimulation of lymph node cells from CY-treated mice was depressed shortly after treatment; however, responses to phytohemagglutinin and three Candida antigens (a cell wall preparation, a membrane preparation, and soluble cytoplasmic substances) recovered, whereas the responses to lipopolysaccharide did not. CY effects on the cutaneous lesion were twofold; first, the number of viable Candida cells in the lesions was much higher in animals receiving CY 3 days before Candida inoculation, and second, the size of the dermal lesion was either greatly enhanced or reduced depending upon the time of CY treatment relative to the number of cutaneous Candida inoculations. CY-treated animals developed higher levels of delayed hypersensitivity to the membrane preparation when infected once cutaneously than did corresponding untreated animals. The number of mice responding with circulating antibodies to soluble cytoplasmic substances after cutaneous inoculation was greatly reduced in CY-treated groups, and this impaired ability to produce antibodies correlated with the poor survival of these mice after intravenous challenge. Our results suggest that the ability to produce antibody at the time of challenge is crucial to successful defense against systemic candidiasis in this murine model.